Displacement and the Humanities: Manifestos from the Ancient to the Present - Isayev, Elena; Jewell, Evan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint brings together the work of practitioners, communities, artists and other researchers from multiple disciplines. Seeking to provoke a discourse around displacement within and beyond the field of humanities, it positions historical cases and debates, some reaching into the ancient past, within diverse geo-chronological contexts and current world urgencies. In adopting an innovative dialogic structure, between practitioners on the ground-from architects and urban planners to artists-and academics working across subject areas, the volume is a proposition to remap priorities for current research agendas; open up disciplines, critically analyse their approaches; address the socio-political responsibilities that we have as scholars and practitioners; and provide an alternative site of discourse for contemporary concerns about displacement. Ultimately, this volume aimed to provoke future work and collaborations-hence, manifestos-not only in the historical and literary fields, but wider research concerned with human mobility and the challenges confronting people who are out of place in terms of rights, protection and belonging.